Modelagem na transferência de cobre e zinco em solos contaminados por dejetos líquidos de suínos - Mallmann, Fábio Joel Kochem (2013)
Soils subjected to successive pig slurry (PS) amendments present zinc (Zn) and copper (Cu) increases, mostly on soil surface layer. The continuous application of PS causes accumulation of these heavy metals (HM) in soil, increasing risks for environmental contamination. Therefore, development of methods to estimate Zn and Cu accumulation in surface layer and their movement in soil is very important for the management planning of PS and of the agricultural soils amended with these residues. The main objective of this work was to model the vertical transport of Zn and Cu in profile of agricultural soils receiving successive application of PS at high, moderate and low doses, evaluating the effects of soil tillage and water absorption by roots on the movement of these HM. We also aimed to predict the long-term accumulation of HM in soil surface and their transport into groundwater, comparing estimated results with the threshold values established for agricultural soils and groundwater by the Conselho Nacional do Meio Ambiente (CONAMA). Two studies were performed on field experiments composed by different PS doses, the first located on an Alfisol in Santa Maria RS, and the second on an Oxisol in Campos Novos SC. Hydro-physical and chemical characteristics of these soils were measured and, accompanied by atmospheric and PS application data sets, were introduced into HYDRUS-1D for parameterization of the two-site model used. In the first study, simulations for next 100 years were performed under scenarios combining two PS doses and four time intervals between soil tillage of the arable layer. The solute transport model used on these simulations was already validated for this local soil in another study. In the second study, the validation of a solute transport model was carried out primarily, following the same approaches used for the Alfisol. Afterwards, root water uptake and root growth modules were introduced to the model. The future scenarios were simulated using applications of different PS doses during the next 50 years. The solute transport model previously validated for the Alfisol was also validated for the Oxisol, and the introduction of the root modules in HYDRUS-1D produced even better results. This increased the usefulness of the model for its use in simulations related to Zn and Cu transport on other contaminated soils. Future scenarios exhibit a great accumulation of these two HM in soil surface layer during the simulated times. Moreover, when soils are submitted to high PS annual doses, its Cu concentrations reached the maximum values established by CONAMA for agricultural soils in approximately 94 years on the Alfisol and in 29 years on the Oxisol. Reduction in PS doses and sporadic soil tillage are strategies that slow the increase of these HM concentrations in soil surface layer, decreasing so the environmental risks and making PS additions on agricultural soils viable for longer time.